Occupational Pulmonary Tuberculosis among BRAC Community Health Workers of Trishal, Bangladesh - Karim, Fazlul; Islam, Qazi Shafayetul; Islam, Md. Akramul; Ahmed, Jalaluddin (BRAC Research and Evaluation Division (RED), 2019)
Different studies reported 2-14 times higher risk of TB for the healthcare workers than the general populations. This poses a serious challenge to the healthcare workers involved in TB control worldwide. BRAG has been using services of thousands of community-based health workers (GHW) known as shasthya shebikas for TB control all over the country. Their continuous exposure to infectious pulmonary TB (PTB) patients might have increased the risk of disease transmission. This concem led RED to implement a pilot study in Trishal upazila to (i) assess the operational feasibility of using GXR (chest X-ray) as a tool for PTB diagnosis, and obtaining and testing sputum samples; and (ii) measure the rate of active TB in different health workers of BRAG. Data were generated through face-to-face interview using structured and semi-structured instruments. Each eligible GHW gave a GXR at a designated private clinic at Trishal. Three independent specialist physicians examined the GXRs. Besides, three sputum samples (night, moming and spot) were collected from each of the study participants, and tested at BRAG field laboratories. Five percent of them were re-tested at an extemal quality assurance laboratory in Mymensingh for quality control. Additional sputum samples of 26 respondents (two from each) were cultured at the national TB programme reference laboratory in Dhaka. Positive agreement of two examiners on an individual GXR or two sputum slides test-positive or one sputum slide test-positive supported by one GXR-positive or one sputum culture-positive was defined as a TB patient. Quantitative data were analyzed by SPSS software, while the qualitative data were handled manually. The estimated prevalence rate of smear-negative PTB among the shasthya shebikas was 1,612.9/100,000. This was 4-fold higher than the prevalence of all forms of TB in the general population of Bangladesh. This implies that the grassroots health workers are at a greater risk of PTB. Qualitative explorations revealed that contact with PTB patients and poverty were major causes of PTB among SSs, warranting appropriate measures for preventing disease transmission.